Boosting biodiesel production over silicon heterojunction with visible light irradiation - Aminul Islam; Teo, Siow Hwa; Md. Tarekul Islam; Easteak Ahamed; Md. Shahinoor Islam; Abdulkareem Ghassan Alsultan; Hadi M. Marwani; Mohammed M. Rahman; Abdullah M. Asiri; Yap, Taufiq Yun Hin; Md. Rabiul Awual (Elsevier Ltd, 2023)
Renewable energy sources offer greater reliability and resilience compared to traditional sources. Biodiesel, derived from renewable resources that absorb carbon dioxide during growth and production, boasts a significantly lower carbon footprint than petroleum-based diesel fuel. Heterojunction photocatalysts have emerged as a promising solution for environmental challenges. This study focused on efficient biodiesel production using visible light-irradiated Si/MgO heterojunctions. The XPS analysis confirmed the crucial role of surface functionality in achieving high photocatalytic efficiency. Transesterification occurs through SiH and SiOH bond formation on the catalyst. Finite-difference time-domain (FDTD) predicts the structure–activity relationship, showing stronger plasmonic nearfields in Si/MgO due to distinct dielectric constants. The Si/MgO photocatalyst exhibited superior photocatalytic activity under visible light, consistent with FDTD results. Biodiesel production was attained to 96% yield using 2 wt% catalysts, a 12:1 M ratio of methanol to Jatropha curcas oil, and a 3.5 hrs reaction time. Therefore, the work provided valuable insights into the mechanism of efficient plasmonic photocatalysis, paving the way for future advancements in novel high-performance photocatalysts.